The clinical course of sarcoidosis: presentation, diagnosis, and treatment in a large white and black cohort in the United States - Judson, M.A.; Boan, A.D.; Lackland, D.T. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: Although numerous reports have described the clinical features of sarcoidosis in various ethnic and racial groups, many have been limited by small size, homogenous populations, and relatively short follow-up periods. We report the clinical characteristics of a large, race-sex-age diverse cohort of sarcoidosis clinic patients followed in a large university medical center for an extended period of time. Methods: This study included clinical data for sarcoidosis patients followed over a 12-year period at a sarcoidosis clinic at the Medical University of South Carolina. Results: 1774 sarcoidosis patients were identified. Black females were more common (44%) than other race/gender combinations (p = 0.01). The diagnosis of sarcoidosis occurred > 3 months after the onset of symptoms in 48% of the cohort and > 1 year after the onset of symptoms in 25%. Anti-sarcoidosis treatment was required in 61% of the patients. Pulmonary function improved over time and the median corticosteroid requirement lessened. Compared to whites, blacks had more advanced radiographic stages of sarcoidosis (p < 0.0001), more organ involvement (p < 0.0001), and more frequently required anti-sarcoidosis medication (p < 0.0001). Compared to women, men had more advanced radiographic stages of sarcoidosis (p < 0.0001). Conclusions: The analysis indicates that sarcoidosis tends to improve over time in terms of pulmonary function and medication requirements.The disease was found to be more severe in blacks than whites.Treatment was not necessarily required. These results provide a comprehensive model of the course and treatment of sarcoidosis in the clinical setting.